RANCANG BANGUN SISTEM LOCK AND CONTROLLING CLASS ROOMS (LCCR) BERBASIS RASPBERRY PI - , MOCHAMAD SUBIANTO; , Dr. Agfianto Eko Putra, M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
An educational institution has several facilities especially classrooms that have the most important role in the learning process. It is therefore necessary that the supervision and control of the learning process is not hampered or disturbed. Several previous studies have made use of a system control room, but still has a highly limitation is the lack of a centralized basis data and still using a computer that has a large size and relatively expensive for a device controller. That requires a system that is less expensive and practical and can be integrated with a centralized basis data that can control the use of the room. Study has been done on the process of controlling a room with all the electronic devices that exist in the room by using a tool called the Raspberry Pi. Raspberry Pi (also known as Raspi) is a SBC (Single Board Computer) developed credit card-sized Raspberry Pi Foundation in the United Kingdom (UK). Raspberry Pi control system assisted by 2 pieces of equipment ie electrical switches and electrical amplifier. Power switch is used to disconnect and connect the AC power. Electrical amplifier is used to increase the DC power of GPIO to 12V DC. Programming to control the Raspberry Pi using the JAVA programming language. Use MySQL database for central data is plased on computer servers so that the concept can be applied to many LCCR room or some Raspberry Pi. A control room and electronic devices that is in the room is very important to reduce negligence by the user.